2014
DOI: 10.1016/j.cortex.2014.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Validation of an integrated method for determining cognitive ability: Implications for routine assessments and clinical trials

Abstract: Introduction Although accurate diagnosis of deficit of mild intensity is critical, various methods are used to assess, dichotomize and integrate performance, with no validated gold standard. This study described and validated a framework for the analysis of cognitive performance. Methods This study was performed by using the GREFEX database (724 controls and 461 patients) examined by 7 tests assessing executive functions. The first phase determined the criteria for the cutoff scores, the second phase, the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 53 publications
1
42
0
4
Order By: Relevance
“…To our knowledge, this major effect has never been previously reported and is consistent with previous studies demonstrating the role of four methodological factors influencing the resulting prevalence of cognitive impairment: control for demographic factors (particularly age and education), procedures controlling for the false-positive rate (adjustment of the number of unpaired scores, computation of domain scores or global score), the size of the control group used to determine the cutoff score, and the threshold used to categorize cognitive score as normal versus impaired [45-47]. Eight studies used norms based on a control group: only 6 of these studies indicated the sample size of this group, which was greater than 500 in only 1 study, indicating that at least 5, and possibly 7, of the 8 studies were at risk of inaccurate determination of the cutoff and consequently inaccurate estimation of the prevalence of post-stroke NCD [45-58]. The effect of post-stroke interval supports the previous observation of an increased incidence of dementia according to post-stroke interval [2].…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…To our knowledge, this major effect has never been previously reported and is consistent with previous studies demonstrating the role of four methodological factors influencing the resulting prevalence of cognitive impairment: control for demographic factors (particularly age and education), procedures controlling for the false-positive rate (adjustment of the number of unpaired scores, computation of domain scores or global score), the size of the control group used to determine the cutoff score, and the threshold used to categorize cognitive score as normal versus impaired [45-47]. Eight studies used norms based on a control group: only 6 of these studies indicated the sample size of this group, which was greater than 500 in only 1 study, indicating that at least 5, and possibly 7, of the 8 studies were at risk of inaccurate determination of the cutoff and consequently inaccurate estimation of the prevalence of post-stroke NCD [45-58]. The effect of post-stroke interval supports the previous observation of an increased incidence of dementia according to post-stroke interval [2].…”
Section: Discussionsupporting
confidence: 70%
“…The second concerns the adoption of a standardized cognitive assessment according to the proposed neuropsychological battery assessing 5 cognitive domains (language, visuo-constructive abilities, memory, action speed, and executive functions), in addition to depression and behavioral changes [49]. The third source of improvement concerns the standardized analysis of a combination of cognitive scores, as proposed in a recent validation study [45]. Finally, common criteria for mild and major post-stroke NCD must be adopted, as recently proposed by the VASCOG group [50].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found that summary scores, such as averaging of z-scores and item response theory score, provided a more accurate determination of the prevalence of cognitive impairment in a very large sample of 461 patients and 724 controls [38]. Although the use of the number of impaired cognitive scores has been demonstrated to be less sensitive than summary scores, the relatively small sample in our study did not allow the use of such sophisticated methods; that, however, will have to be implemented in further studies on the optimization of operationalization of criterion of mild cognitive impairment Q2 .…”
Section: Discussionmentioning
confidence: 99%
“…1 Briefly, the 19 transformed scores (log transformation for the completion time in the Trail Making and Stroop tests; Box-Cox transformation for the other scores) 39 of the 7 cognitive tests were entered in a series of linear regression analysis (1 per score) with age, educational level, gender, and an interaction term (age × education level) and significant factors in healthy controls were retained. Regression coefficients computed in healthy controls were used to calculate standardized residuals, that is, z scores (poor performance corresponded to a negative z score).…”
Section: Statisticsmentioning
confidence: 99%
“…30 For this purpose, we used previously validated diagnostic criteria of executive functions deficits and a recently described statistical methodology permitting to control the effect of confounders on test performance on a large sample of patients with TBI compared with healthy individuals. 1 Briefly, the transformed scores of cognitive and behavioral measures were entered in a series of linear regression analysis with age, educational level, gender, and an interaction term (age × education level) and significant factors in healthy controls were retained. Regression coefficients computed in healthy controls were used to calculate standardized residuals, that is, z scores.…”
Section: E11mentioning
confidence: 99%